2016
DOI: 10.1016/j.matdes.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Porous Mn-doped ZnO nanoparticles for enhanced solar and visible light photocatalysis

Abstract: Porous Mn-doped ZnO (ZnO:Mn) nanoparticles with an average diameter of ca. 21 nm were prepared by a simple and cheap solvothermal process involving no templates, post-synthetic annealing or etching. The particles produced were characterized by XRD, Raman spectroscopy, SEM, TEM, XPS, diffuse reflectance spectroscopy and BET surface area measurements and the effects of Mn 2+-doping on the structural, optical and photocatalytic properties of ZnO particles were investigated. The particles doped with 3 mol% Mn 2+ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(64 citation statements)
references
References 50 publications
2
61
0
1
Order By: Relevance
“…In a similar manner as described before [7,13], ZnO rods were synthesized by a solvothermal method based on the hydrolysis of Zn(OAc) 2 . Typically, in a three-necked flask equipped with a condenser and a dropping funnel, Zn(OAc) 2 ·2H 2 O (511 mg, 2.33 mmol) was dissolved in 35 mL ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar manner as described before [7,13], ZnO rods were synthesized by a solvothermal method based on the hydrolysis of Zn(OAc) 2 . Typically, in a three-necked flask equipped with a condenser and a dropping funnel, Zn(OAc) 2 ·2H 2 O (511 mg, 2.33 mmol) was dissolved in 35 mL ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar manner as described before [7,13], the photocatalytic activity was evaluated by the degradation of an aqueous Orange II solution (10 mg/L) at room temperature under solar light irradiation. In a typical experiment, the ZnO:Ce rods (30 mg) were dispersed in 30 mL Orange II aqueous solution and the suspension was magnetically stirred under ambient conditions for 80 min in the dark to reach an adsorption-desorption equilibrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping of ZnO NPs with transition metal ions affects the optical and photocatalytic activity properties by shifting the optical absorption toward the visible region . Hence, recently, the focus of many researchers has turned to doping of ZnO NPs with transition metals such as Mn, Cr, Fe, Ti, V, Co, Ni, Cu, Y, Zr, Nb, Pd, Ag and Cd . Copper (Cu) is considered as one of the most effective means of doping because of its physical and chemical properties are similar to those of zinc (Zn), its inexpensiveness and natural abundance can improve absorption, emission and photocatalytic activity of ZnO NPs .…”
Section: Introductionmentioning
confidence: 99%
“…showed that Mn-doped ZnO increased the surface area, decreased electron-hole recombination, and finally improved the catalytic activity for methylene orange degradation [11]. Based on the above considerations, we choose the manganese as a dopant to improve the performance of Zn(O,S).…”
mentioning
confidence: 99%